Application of the screening test principles to screening for neonatal hypoglycemia - Alsweiler, J. M.; Heather, N.; Harris, D. L.; McKinlay, C. J. D. (Frontiers in Pediatrics, 2022)
Severe and prolonged neonatal hypoglycemia can cause brain injury, while the long-term consequences of mild or transitional hypoglycemia are uncertain. As neonatal hypoglycemia is often asymptomatic it is routine practice to screen infants considered at risk, including infants of mothers with diabetes and those born preterm, small or large, with serial blood tests over the first 12-24 hours after birth. However, to prevent brain injury, the gold standard would be to determine if an infant has neuroglycopenia, for which currently there is not a diagnostic test. Therefore, screening of infants at risk for neonatal hypoglycemia with blood glucose monitoring does not meet several screening test principles. Specifically, the long-term neurodevelopmental outcomes of transient neonatal hypoglycemia are not well understood and there is no direct evidence from randomized controlled trials that treatment of hypoglycemia improves long-term neurodevelopmental outcomes. There have been no studies that have compared the long-term neurodevelopmental outcomes of at-risk infants screened for neonatal hypoglycemia and those not screened. However, screening infants at risk of hypoglycemia and treating those with hypoglycaemic episodes to maintain the blood glucose concentrations ≥ 2.6 mmol/L appears to preserve cognitive function compared to those without episodes. This narrative review explores the evidence for screening for neonatal hypoglycemia, the effectiveness of blood glucose screening as a screening test and recommend future research areas to improve screening for neonatal hypoglycemia. Screening babies at-risk of neonatal hypoglycemia continues to be necessary, but as over a quarter of all infants may be screened for neonatal hypoglycemia, further research is urgently needed to determine the optimal method of screening and which infants would benefit from screening and treatment.